Testing the attention-distractibility trait. - Meier, Matt E. (Memory & Cognition, 2021)
Forster and Lavie (Journal of Experimental Psychology: Learning, Memory, and Cognition, 40[1], 251–260, 2014; Psychological Science, 27[2], 203–212, 2016) found that task-irrelevant distraction correlated positively with a measure of mind-wandering and a report of attention-deficit/hyperactivity disorder (ADHD) symptomology. Based primarily on these results, Forster and Lavie claimed to establish an attention-distractibility trait. Here, I tested whether these associations could be distinguished from associations with working memory capacity and task-relevant distraction (measured with an antisaccade task). With data collected from 226 subjects (ns differ among analyses), the results from the current study suggest that the measures of task-irrelevant distraction and working memory capacity were not (or only very weakly) associated with measures of mind wandering (measured both with a stand-alone questionnaire and in-task thought probes) and ADHD symptomology. Task-relevant interference (i.e., antisaccade accuracy) was associated with mind-wandering reports from in-task thought probes (presented in a separate task), but not the stand-alone mind wandering questionnaire or ADHD symptomology. Additionally, the measure of irrelevant-distraction exhibited low internal consistency suggesting that (as measured) it may not be a suitable individual difference measure. [Preregistration, data, analysis scripts and output are available via the Open Science Framework: https://osf.io/bhs24/].